Research on Permeability Enhancement Model of Pressure Relief Roadway for Deep Coal Roadway Strip - Zhonghua Wang; Jianjun Cao; Jun Liu; Chengcheng Li (Geofluids)
Aiming at the problem of permeability enhancement in deep coal roadway strip, it proposed a pressure relief roadway permeability enhancement model, and the model was verified through experiments, theoretical calculations, and field tests. The experiment reveals that the unloading of gas-containing coal can achieve the effect of permeability enhancement. Theoretical calculation shows that with the increase of the distance from the coal seam, the overlying coal seam’s permeability enhancement multiple and the width of the significant permeability enhancement zone gradually decrease, and the width of the general permeability enhancement zone gradually increases and then stabilizes. Field tests show that the pressure relief roadway is arranged 9 m directly below the coal seam; the overlying coal strata has a significant pressure relief and permeability enhancement effect. This research can provide reference value for the high-efficiency permeability enhancement in the deep coal roadway strip.